(untitled) (Proceedings of International Educators Conference, 2024)
Alcoholism (lat. alcoholismus), as well as drunkenness, chronic alcoholism, chronic alcohol intoxication, alcoholism, alcohol toxicomania, etc. is a chronic progressive mental illness, a type of toxicomania, addiction to alcohol (ethyl alcohol) and mental and physical dependence on it. is characterized by Alcoholism is characterized by loss of control over the amount of alcohol consumed, increased tolerance to alcohol (an increase in the amount of alcohol required to maintain satiety), abstinence syndrome, toxic organ damage, and some of the effects that occur during intoxication. characterized by inability to remember events.